2003
DOI: 10.1183/09031936.03.00050903
|View full text |Cite
|
Sign up to set email alerts
|

Effects of erythromycin onPseudomonas aeruginosaadherence to collagen and morphologyin vitro

Abstract: The airways of patients with bronchiectasis and cystic fibrosis are often chronically colonised by Pseudomonas aeruginosa (PA), which is virtually impossible to eradicate. Low-dose erythromycin (EM), for unknown mechanisms, is efficacious in bronchiectasis and diffuse panbronchiolitis.In this study, an in vitro model to investigate PA adherence to human type IV basement collagen was developed by using scanning electron microscopy (SEM). There were significantly less PA bacilli per 20 random SEM fields (4,0006)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 27 publications
1
25
0
2
Order By: Relevance
“…Decreases in cell size (both rod diameter and length) have been detected in Legionella pneumophila treated with the peptidoglycan synthesis inhibitor ampicillin [141], and P. aeruginosa treated with the protein synthesis inhibitor erythromycin [167]. The cause(s) of these decreases in size was not established [141,167]. Lastly, a combination of both increased and decreased cell size has been observed in Staphylococcus aureus populations treated with novobiocin [168].…”
Section: Altered Cell Sizementioning
confidence: 77%
See 1 more Smart Citation
“…Decreases in cell size (both rod diameter and length) have been detected in Legionella pneumophila treated with the peptidoglycan synthesis inhibitor ampicillin [141], and P. aeruginosa treated with the protein synthesis inhibitor erythromycin [167]. The cause(s) of these decreases in size was not established [141,167]. Lastly, a combination of both increased and decreased cell size has been observed in Staphylococcus aureus populations treated with novobiocin [168].…”
Section: Altered Cell Sizementioning
confidence: 77%
“…If, however, the enlarged bacteria are examined in cross-section, the increase in size can usually be attributed to inhibition of cell separation ('pseudomulticellular bacteria') [127,158], or osmotic swelling ('spheroplasts' or 'protoplasts') [84]. Decreases in cell size (both rod diameter and length) have been detected in Legionella pneumophila treated with the peptidoglycan synthesis inhibitor ampicillin [141], and P. aeruginosa treated with the protein synthesis inhibitor erythromycin [167]. The cause(s) of these decreases in size was not established [141,167].…”
Section: Altered Cell Sizementioning
confidence: 99%
“…Adherence to basement membrane is, therefore, an important issue that has not been studied previously. Therefore, the authors have recently established a model to study bacterial adherence to basement membrane collagen and applied this to evaluate the effects of various chemicals on the adherence of P. aeruginosa to collagen in vitro [10].…”
mentioning
confidence: 99%
“…aeruginosa are well described [117] with inhibitory effects on flagellin expression, exoenzyme production [118] and collagen adherence [119]. Multiple studies have demonstrated that macrolide antibiotics interfere with the quorum sensing circuitry of P. aeruginosa in vitro [20,21,43,74,117,119,120] [ 17,20,[120][121][122][123].…”
Section: Quorum Sensing Inhibition With Macrolide In Vitromentioning
confidence: 99%
“…Multiple studies have demonstrated that macrolide antibiotics interfere with the quorum sensing circuitry of P. aeruginosa in vitro [20,21,43,74,117,119,120] [ 17,20,[120][121][122][123]. Macrolide antibiotics have been shown to inhibit the expression of rhlAB (rhamnolipid), lasR, rhlR, lasI and rhlI [21] as well as the production of elastase, pyocyanin [120]) and quorum sensing molecules [20,21].…”
Section: Quorum Sensing Inhibition With Macrolide In Vitromentioning
confidence: 99%